PENGARUH GAMIFIKASI QUIZ ZEP TERHADAP MOTIVASI BELAJAR SISWA PADA MATERI MEDIA DIGITAL KELAS X KULINER SMK NEGERI 3 KUPANG - Ledoh, Pingky Kimberli; J. Taku Neno, Katrin; Y. A Fallo, Diana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of Quiz Zep gamification on students’ learning motivation in Digital Media subjects for Grade X Culinary students at SMK Negeri 3 Kupang. The study was motivated by the low level of student learning motivation, characterized by passive participation, low enthusiasm, and limited engagement in classroom activities. This research employed a quantitative approach using a quasi-experimental method with a One-Group Pretest–Posttest Design. The sample consisted of 24 students from Grade X Culinary 2 selected through purposive sampling. Data were collected using learning motivation questionnaires, observations, and documentation. The collected data were analyzed using descriptive statistics and a Paired Sample t-Test. The results showed that Quiz Zep gamification had a significant effect on students’ learning motivation. The hypothesis test yielded a significance value (Sig. 2-tailed) of 0.000, which was lower than 0.05, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. The implementation of Quiz Zep increased students’ attention, engagement, confidence, and satisfaction during the learning process. The gamification elements such as points, leaderboards, challenges, and instant feedback created a more interactive, enjoyable, and motivating learning environment. Therefore, Quiz Zep gamification can be used as an innovative learning medium to enhance students’ learning motivation in Digital Media subjects.